Zebrafish Polymerase Theta and human Polymerase Theta: Orthologues with homologous function - Corey Thomas; Sydney Green; Lily Kimball; Isaiah R. Schmidtke; Lauren Rothwell; Makayla Griffin; Ivy Par; Sophia Schobel; Yayleene Palacio; Jamie B. Towle-Weicksel; Steven E. Weicksel (PLoS ONE, 2025)
DNA Polymerase Theta (Pol θ) is a conserved an A-family polymerase that plays an essential role in repairing double strand breaks, through micro-homology end joining, and bypassing DNA lesions, through translesion synthesis, to protect genome integrity. Despite its essential role in DNA repair, Pol θ is inherently error-prone. Recently, key loop regions were identified to play an important role in key functions of Pol θ. Here we present a comparative structure-function study of the polymerase domain of zebrafish and human Pol θ. We show that these two proteins share a large amount of sequence and structural homology. Using a classical biochemical approach we observe that zebrafish Pol θ displays behavior characteristic of human Pol θ, including DNA template extension in the presence of different divalent metals, microhomology-mediated end joining, and translesion synthesis. These results will support future studies looking to gain insight into Pol θ function on the basis of evolutionarily conserved features.